The influence of ageing treatment on the microstructural evolution and the mechanical properties of the TI-6AL-4V alloy - Mostert, R.J. (Roelf) (University of Pretoria, 2025)
Dissertation (MSc (Applied Science Metallurgy))--University of Pretoria, 2017.